2014
DOI: 10.1182/blood-2013-06-511527
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal leukemia-stroma VCAM-1/VLA-4-dependent activation of NF-κB mediates chemoresistance

Abstract: Key Points VCAM-1/VLA-4 triggers reciprocal NF-κB activation in leukemia and stromal cells and mediates cross-talk between leukemia and stromal cells. VCAM-1/VLA-4 and NF-κB signaling plays a pivotal role in the development of leukemia chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
221
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 44 publications
9
221
0
Order By: Relevance
“…There is a large body of evidence indicating that the AML cell genotype underlies observed variations in the response of patients to chemotherapy; it is therefore not surprising that leukemia cells can modify their BM microenvironment, and thus "educate it" to promote leukemia progression. We have previously demonstrated that reciprocal interactions between the BM microenvironment and AML cells can modify the BM-MSC transcriptome promoting resistance to chemotherapy via processes involving cell-to-cell and cell/matrix interactions, as well as paracrine and autocrine signaling [1]. Similarly, several reports have described critical molecular changes in the stroma of solid tumors [2][3][4] and more recently; it has been shown in colorectal cancer (CRC) that genes expressed by stromal cells are better predictors of response to therapy and disease prognosis than genes expressed by epithelial tumor cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence indicating that the AML cell genotype underlies observed variations in the response of patients to chemotherapy; it is therefore not surprising that leukemia cells can modify their BM microenvironment, and thus "educate it" to promote leukemia progression. We have previously demonstrated that reciprocal interactions between the BM microenvironment and AML cells can modify the BM-MSC transcriptome promoting resistance to chemotherapy via processes involving cell-to-cell and cell/matrix interactions, as well as paracrine and autocrine signaling [1]. Similarly, several reports have described critical molecular changes in the stroma of solid tumors [2][3][4] and more recently; it has been shown in colorectal cancer (CRC) that genes expressed by stromal cells are better predictors of response to therapy and disease prognosis than genes expressed by epithelial tumor cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…133 Reciprocal activation of NF-kB signaling via VCAM-1/very late antigen 4 (VLA-4) interaction occurs in BMSCs and AML cells, and blockade of stromal NF-kB signaling can sensitize AML cells to chemotherapy. 134 Likewise, leukemic and stromal cell interaction via VLA-4 and fibronectin interferes with druginduced apoptosis. Combined treatment of cocultures with VLA-4-specific antibodies and cytarabine improves survival, and patients with VLA-4-negative AML have a favorable prognosis.…”
Section: The Niche In Response To Chemotherapymentioning
confidence: 99%
“…Due to this effect, elderly leukemia patients have relatively few BM adipocytes, which tend to increase with age. Additionally, a growing body of evidence indicates that leukemia cells can regulate their microenvironment to increase their chances of proliferation and survival [10,11]. Therefore, the mechanisms used by leukemic cells to inhibit the differentiation of BM-MSCs into adipocytes could prove useful for HSC engrafts during the transplantation process.…”
Section: Introductionmentioning
confidence: 99%